ANALISIS PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI RISIKO TERHADAP MINAT BELI ULANG KONSUMEN DENGAN KEPERCAYAAN SEBAGAI VARIABEL PERANTARA (STUDI PADA LAYANAN SHOPEE PAYLATER) - Almanita Nurajizah; Farida Indriani (Diponegoro Journal of Management, 2023)
ABSTRACT Shopee provides various payment options to make it easier for consumers to complete transactions, one of which is the Shopee Pay Later service. These more accessible payment options do not guarantee security for their users because there are still many problems regarding account hacking, fraud, and abuse of Pay Later balance limits experienced by consumers. This study aims to analyze the effect of perceived ease of use and perceived risk on consumer repurchase intentions using trust as an intermediary variable. This research was conducted using a quantitative method, using a questionnaire method, and using 130 respondents as a sample with a sampling technique called purposive sampling. The data analysis tool used in this study was AMOS 22 Structural Equation Modeling (SEM). The results of the analysis in this study show that: 1) Perceived ease of use has a positive and significant effect on trust. 2) Perceived risk does not affect Trust. 3) Trust has a positive and significant effect on Repurchase Intention. 4) Perceived Ease of Use has a positive and significant effect on Repurchase Intention. 5) Perceived Risk does not affect Repurchase Intention.